Relationship between organizational politics perceptions and employees' performance: Mediating role of social exchange perceptions - Mahmood Ahmad Bodla; Talat Afza; Rizwan Qaisar Danish (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
Perceptions of Organizational politics are very important aspect of Organizational life with respect to its members as these influence various processes which ultimately affect performance of employees. Previous studies have investigated impact of political perceptions either on extra role performance of employees (exhibited through organizational citizenship behaviors) or various other attitudes and behaviors. This study investigates the relationship of perceptions of organizational politics with multidimensional performance of employees which is measured through organizational citizenship behavior-individual as well as organizational and in role performance of employees simultaneously. Moreover the process through which these perceptions operate is also investigated in the light of social exchange theory and reciprocity norms. The data was collected through self-administered questionnaires from employees working in different organizations at national level and was used as aggregate. Overall 1360 surveys were distributed among which 1163 useable questionnaires (for a response rate of 85.51%) were returned filled and were entered into SPSS 20 for analysis. AMOS 20 was used for developing structural and measurement model in structural equation modeling and for testing mediation through bootstrap strategy. The standardized indirect effect revealed that perceptions of social exchange fully mediate the relationship between perceptions of organizational politics and employees' performance. The implications, limitations and future directions are also provided.
Keywords: 330; perceptions; organizational politics; social exchange; employee's performance